Brain Computer Interface Controlled Wheel Chair. Issue 1 (July 2021) - Sharma, Himanshu; Mahajan, Rahul; Sakthivel, G; Saravanakumar, D; Raghukiran, N
Abstract: Brain computer interface wheel chair specially designed for paralyzed and disabled person who are not capable to operate normal wheel chair. This wheel chair is based on (BCI) Brain computer interface, it can control the wheel chair from brain neurons by the help of BCI. Brain computer interface (BCI) is a computer-based system that obtain brain signal that can be controlled by Neurosky Sensor which is an electrophysiological process to archive the electrical activity of the brain. A BCI system recognize users to grant their determination by study their brain signals. This technology is very helpful for paralyzed and disabled person they can easily moves wheel chair in any direction.